Integration of Sustainable Finance in KBMI 4 State-Owned Banks in Indonesia - Hardy R. Hermawan; Jerry Marmen; Fangky A. Sorongan (Journal of Business, Finance, and Banking, 2026)
The Indonesian banking industry faces demands to integrate environmental, social, and governance (ESG) principles in line with OJK regulations and the Sustainable Finance Taxonomy. This study analyzes the implementation of sustainable finance at three state-owned banks in KBMI category 4—Bank Mandiri, BRI, and BNI—during the 2022–2024 period. The method used is content analysis of sustainability reports, quantified using content analysis scoring based on GRI indicators and OJK regulations. The results show that Bank Mandiri excels in green financing, BRI excels in microfinance inclusion, and BNI plays a role as a development agent. Disclosure scores range from 70–77 percent, reflecting formal compliance but suboptimal in depth, transparency, and impact measurement. Theoretical analysis using Sustainable Finance Disclosure Theory, Greenwashing Typology, and the ESG Integration Maturity Model indicates that regulatory pressures, market expectations, and reputational demands influence the quality of ESG reporting. All three banks are still in the transition stage from compliance to impact-based integration. External verification, consistency of quantitative indicators, and measurement of tangible results are required so that sustainability reporting functions not merely as a normative obligation, but as an instrument of strategic legitimacy and ongoing accountability.